-4(T -6) - (T+6)= 7 -4T -24 -T -6 = 7 - 5T - 30 = 7 + 30 + 30 - 5T = 37 is this going the right way pls help

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

you made an error in line 2... you multiplied -4 by -6 in line 1 and replaced it with -24 in line 2... should have been +24

-4t + 24 + t + 6 = 7 -4t + t+ 24 + 6 = 7 -3t + 30 = 7 -3t - 30 + 30 = 7 - 30 -3t = -23 Divide t = 7.8 Now switch t = 11/5

fix that and then do the simplifying again...

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.